Effect of modified laparoscopic hysterectomy on pelvic floor function: A retrospective observational study. Issue 8 (February 2019) - Lee, Chung-Yuan; Tseng, Chih-Jen; Chang, Chia-Hao; Lee, Meng-Chih; Ou, Yu-Che; Yang, Shun-Fa
Abstract : Abstract: Hysterectomy is a potential risk factor for subsequent surgery for pelvic organ prolapse, especially when the prolapse exists before hysterectomy. Women without prolapse before hysterectomy may also experience prolapse after hysterectomy. This study aimed to describe a surgical modification of laparoscopic colposuspension with round ligaments after hysterectomy in women without preexisting genital prolapse and to evaluate the initial surgical results in these patients. We reviewed data of 54 patients who underwent laparoscopic hysterectomy with colposuspension with unilateral or bilateral round ligaments after hysterectomy at Chia-Yi Chang Gung Memorial Hospital from July 2012 to March 2015. Vaginal length was measured before and after colposuspension after complete hysterectomy. Preoperative characteristics of the patients, perioperative quality, postoperative outcomes, and vaginal length differences were analyzed. Vaginal length increased by a mean of 2.59 cm after colposuspension. The mean extra-operative time needed for laparoscopic colposuspension was about 10 minutes. No severe complications were reported in our patients, and we did not find any cystocele after completing vaginal cuff suspension to the round ligament. The vaginal apex level was maintained in our modified laparoscopic hysterectomy. Therefore, laparoscopic colposuspension with round ligaments is a promising option as a routine, first-line standard procedure in younger women without genital prolapse to maintain an acceptable vaginal length after laparoscopic hysterectomy.